Spittlebugs of Mediterranean Olive Groves: Host-Plant Exploitation throughout the Year - Nicola Bodino; Vincenzo Cavalieri; Crescenza Dongiovanni; Matteo Alessandro Saladini; Anna Simonetto; Stefania Volani; Elisa Plazio; Giuseppe Altamura; Daniele Tauro; Gianni Gilioli; Domenico Bosco (Insects, 2020)
Spittlebugs are the vectors of the bacterium Xylella fastidiosa Wells in Europe, the causal agent of olive dieback epidemic in Apulia, Italy. Selection and distribution of different spittlebug species on host-plants were investigated during field surveys in 2016−2018 in four olive orchards of Apulia and Liguria Regions of Italy. The nymphal population in the herbaceous cover was estimated using quadrat samplings. Adults were collected by sweeping net on three different vegetational components: herbaceous cover, olive canopy, and wild woody plants. Three species of spittlebugs were collected: Philaenus spumarius L., Neophilaenus campestris (Fallén), and Aphrophora alni (L.) (Hemiptera: Aphrophoridae). Philaenus spumarius was the predominant species both in Apulia and Liguria olive groves. Nymphal stages are highly polyphagous, selecting preferentially Asteraceae Fabaceae plant families, in particular some genera, e.g., Picris, Crepis, Sonchus, Bellis, Cichorium, and Medicago. Host-plant preference of nymphs varies according to the Region and through time and nymphal instar. In the monitored sites, adults peak on olive trees earlier in Apulia (i.e., during inflorescence emergence) than in Liguria (i.e., during flowering and beginning of fruit development). Principal alternative woody hosts are Quercus spp. and Pistacia spp. Knowledge concerning plant selection and ecological traits of spittlebugs in different Mediterranean olive production areas is needed to design effective and precise control strategies against X. fastidiosa vectors in olive groves, such as ground cover modifications to reduce populations of spittlebug vectors.